Empirically examining the impact of corporate social responsibility on financial performance: evidence from Indian steel industry - Nripinder Kaur; Vikramjit Singh (Emerald Publishing Limited, 2020)
This paper aims to examine the impact of corporate social responsibility (CSR) on financial performance (FP) of Indian steel industry in terms of value-added (VAM), profitability (PM), market (MM) and growth measures (GM).It is an empirical study using secondary data of 40 companies for 14 years collected from CSR/annual reports/official websites of the companies and Prowess database. The panel regression analysis, MANOVA and univariate ANOVA have been conducted to examine the impact of CSR on FP.The result indicates a positive impact of CSR on FP in terms of VAM, PM and GM, thereby indicating that more investments in CSR will generate wealth for shareholders, enhance profitability and sales. Moreover, this study shows no noticeable relationship between CSR and MM.This study contributes to the literature on the CSR–FP relationship and also has implications for managers, investors and other stakeholders. Companies with higher CSR rating create a brand image, attract proficient employees, get greater profit, loyal customers and have less possibility of bribery and corruption. This study may result in being influential to companies confined not only to this sector but also reaching to the others, thus inspiring them to contribute their share of profit for the welfare of society.To the best of the authors' knowledge, it is the first comprehensive study to examine the impact of CSR on FP of Indian steel industry by considering four dimensions for measuring FP. It provides evidence about the relationship between CSR and FP.